The Inclusion of Thinking Skills: A Panacea for Improving Instructional Practices in Nigerian Secondary School Education - (:unkn) unknown (My University, 2018)
Having critically studied the current New Secondary School Curriculum (NSSC), it is glaring that there was neither the inclusion nor any consideration given to Thinking Skills. Rather, much emphasis was made on IT and Entrepreneurial skills. Thus, the question is: how can we teach these subjects without emphasising thinking skills, and teaching students to be great critical thinkers using thinking skills?" It is on this ground that this paper is conceptualised to call for a review of the NSSC to include Thinking Skills, so as to create an equilibrium in the teaching and learning process. This will make the students problem solvers and it will reposition them to be invaluable assets to the Nigerian society and beyond. This paper examines such issues as the thinking skills initiative, adoption of thinking points and maps in the classroom, a theoretical review of teaching thinking skills in schools, inclusion of thinking skills in the UK and the new secondary school curriculum in Nigeria. Lastly, recommendations are made on the benefits of thinking skills inclusion in the teaching curriculum.
Keywords: African Research